A systematic assessment of 'Axial Age' proposals using global comparative historical evidence - Mullins, D; Hoyer, D; Collins, C; Currie, T; Feeney, K; Francois, P; Savage, P; Whitehouse, H; Turchin, P (SAGE Publications, 2018)
The ‘Axial Age’ refers to a historical period in the mid-first millennium BCE during which a cluster of changes in cultural traditions are said to have occurred in some of the complex social formations in the areas that are today China, Greece, India, Iran, and Israel-Palestine. This period is said to have witnessed an ‘axial’ or ‘pivotal’ transformation in the relationship between rulers and ruled and laws and customs together with the emergence of a new form of moralising religion and ideology, as manifested in Buddhism, Confucianism, Hinduism, Judaism, Platonism, and Zoroastrianism. Much Axial Age scholarship attempts to characterize these changes, starting with the argument that numerous major religious figures promoting similar moralizing and equity-promoting ideologies emerged at roughly the same time in a handful of arguably disconnected societies, ultimately morphing into some of the world's most widespread ideologies. For example, Christianity, Islam, and Buddhism all trace their roots to this period.